The association between the miR-146a rs2910164 C>G polymorphism and Kawasaki disease in a southern Chinese population. Issue 4 (3rd July 2018) - Zhang, Li; Wang, Jinxin; Che, Di; Wang, Yanfei; Rong, Xing; Pi, Lei; Xu, Yufen; Li, Wei; Huang, Ping; Chu, Maoping; Gu, Xiaoqiong
Abstract : miR-146a plays a critical role in innate immune and inflammatory responses. Kawasaki disease involves immune-mediated inflammatory responses, which leads to vascular endothelial injury. However, there has been no study on the association between the miR-146a rs2910164 C>G polymorphism and Kawasaki disease risk. We enrolled 532 Kawasaki disease patients and 623 healthy controls from southern Chinese population, and the miR-146a rs2910164 C>G polymorphism was genotyped by the TaqMan method. There was no evidence that this polymorphism was associated with Kawasaki disease. Stratified analysis also showed no significant association. The present study indicates that the miR-146a rs2910164 C>G polymorphism may not be associated with Kawasaki disease in the southern Chinese population. Larger multicenter studies are needed to confirm our conclusions.